Desenvolvimento de uma técnica de medição de concentração e vazão mássica em soluções salinas - Caldas, Allan Giuseppe de Araújo (2021)
In this work, it is proposed to develop a technique for measuring concentration and mass flow in saline solutions, especially in refrigeration systems that use the mixture of the water lithium bromide pair. The determination of concentration and mass flow is of fundamental importance in the design of refrigeration systems by vapor absorption, as the measurements of these parameters enable the construction of a control for optimized system operation. The experimental bench used in the research, which simulates one of the sections of an absorption refrigeration unit, was developed by our research group at the Federal University of Paraíba - UFPB on the premises of the North / Northeast Natural Gas Cooperative Research Network building RECOGÁS - N/NE, present at the Sustainable Energy Institute (IES). The developed technique makes it possible to remedy difficulties found in measuring concentration (by means of a non-invasive capacitive sensor) and the mass flow of fluids (liquids) in refrigeration systems since, machines that operate under the absorption cycle, if the concentration of the solution is too high, crystallization of the working fluid may occur. This study will describe all the aspects that will culminate with the purpose of the work, corroborating its functioning and, as a consequence, analyze all the aspects found throughout this research to obtain the objective of the present work.